Efficient intra-household allocation of parental leave - Juliane Parys; Gregor Schwerhoff (Institute for the Study of Labor (IZA), 2010)
We propose a model of how parents resolve conflicts about sharing the negative short and long-term consequences from parenthood-related career interruptions on earnings. We introduce childcare sharing in a collective model of household behavior with public consumption as in Blundell, Chiappori, and Meghier (2005). Conceptually, the solution to the household problem can be thought of as a two-stage process: Parents first agree on public expenditures on professional childcare; then, conditional on the level of public consumption and the budget constraint stemming from stage one, parents determine their individual job absence durations and private consumption shares. Using relative income measures from German parental benefit data as distribution factors, we find evidence for Pareto efficiency in childcare sharing. More precisely, households with higher total incomes purchase more professional childcare, and changes in distribution factors shift the conditional parental leave allocation in favor of the partner whose relative income increased.
urn:nbn:de:101:1-201010132689
Keywords: D13; J12; J13; 330; childcare; collective model; conditional sharing rule; intra-household allocation